Boosting of Dissipated Renewable Energy Systems Towards Sustainability in Kazakhstan - Khabdullina Guldana; Paule Dace; Pakere Ieva; Khabdullin Asset; Blumberga Dagnija (Environmental and Climate Technologies)
The study aims to develop a methodology for selecting and justifying a multi-energy hub based on renewable energy sources for agricultural complex. The methodology has an international dimension and was tested for the pilot case of the study in an agricultural site in Kazakhstan. The methodology consists of two parts. With the help of the EnergyPro software package, simulation of technical and economic analysis and optimization of energy hub operation for several different energy generation units was carried out. During the simulation, four different scenarios of an energy hub based on solar and wind energy, biomass and heat pump as well as coal-based fossil energy sources were considered. The second part of the methodology was based on the economic justification of climate-neutral technological solutions using multi-energy hubs in the agriculture sector. Climate neutrality diagram was created by use of GHG emission trading experience for a detailed technical and economic analysis and selection of the best renewable sources from various installation sites. Results show that the most promising and cost-effective option is the scenario with an integrated wind park, heat pump and biomass boiler.